Measurement properties of instruments for migraine impact in Brazil: a systematic review (Research, Society and Development, 2022)
Objective: To critically appraise, compare and summarize the quality of the measurement properties of all Patient-Reported Outcome Measures translated and validated for the Brazilian population that assess the impact of migraine. Background The evaluation of measurement properties of Patient-Reported Outcome Measures is needed for professionals and researchers to select instruments that ensure quality of results. Thus, reliable instruments are important to provide information on the impact of migraine. Methods: The search was conducted in MEDLINE/Pubmed, Web of Science, LILACS, and Embase databases. We included studies evaluating measurement properties of PROMs that assessed the impact of migraine and were validated for Brazil. Methodological quality, risk of bias, and quality of evidence were assessed following the Consensus-based Standards for Selecting Health Measurement Instruments for systematic reviews of Patient-Reported Outcome Measures Results: A total of 112 studies identified, and four were included. Three instruments were analyzed: Headache Impact Test, which presented a serious risk of bias with moderate quality of evidence; Pediatric Migraine Disability Assessment, which presented an extremely serious risk of bias and very low quality of evidence; and the Headache Disability Inventory¸ which presented a very serious risk of bias and low quality of evidence. Conclusion: The three instruments evaluated had important limitations regarding quality of evidence. The Headache Impact Test was the most recommended instrument because it presented a moderate quality of evidence.